CONFINED AND SUSTAINABLE? A CRITIQUE OF RECENT PASTORAL POLICY FOR REINDEER HERDING IN FINNMARK, NORTHERN NORWAY - Marin, Andrei F. (2006)
An increasing number of development plans and strategies for pastoral communities have failed to ensure the sought sustainability, especially in ecosystems characterized by fluctuating environmental conditions. Many of these strategies are centered on a policy of confining, controlling and settling the nomadic herders.